2019
DOI: 10.4102/ajlm.v8i1.743
|View full text |Cite
|
Sign up to set email alerts
|

Morphological patterns of anaemia among pregnant women from Sudan

Abstract: BackgroundMorphological patterns of anaemia in pregnancy are considered essential for classification, diagnosis and management of patients, especially in regions with high maternal mortality like Sudan.ObjectivesThis study evaluated morphological patterns of anaemia among pregnant women in Sudan and morphological differences across characteristics of participants.MethodsThis cross-sectional study was conducted from September 2016 to February 2017. A total of 200 women were selected according to specific criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Lower concentration of the haemoglobin in the blood affects the circulation of oxygen throughout the body including the brain which limits the maternal and birth outcomes, leads to high morbidity and mortality among mothers and neonates, reduces the working ability and productivity including learning capacity (Harding et al, 2017). Anaemia depresses the immune system and increases the chances of morbidity both in mothers as well as neonates (Abusharib, 2019). It further influences cognitive and intellectual development, socio-economic growth, gross domestic products, and ultimately delay achieving developmental targets including Sustainable developing Development Goals [SDG](Department of Health Services, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lower concentration of the haemoglobin in the blood affects the circulation of oxygen throughout the body including the brain which limits the maternal and birth outcomes, leads to high morbidity and mortality among mothers and neonates, reduces the working ability and productivity including learning capacity (Harding et al, 2017). Anaemia depresses the immune system and increases the chances of morbidity both in mothers as well as neonates (Abusharib, 2019). It further influences cognitive and intellectual development, socio-economic growth, gross domestic products, and ultimately delay achieving developmental targets including Sustainable developing Development Goals [SDG](Department of Health Services, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, it was lower than one reported by Abusharib in Sudan who noted that 58% had a dimorphic pattern (microcytic and macrocytic), followed by 25% with a microcystic pattern and 10% with a macrocytic pattern and 7% with a normocytic pattern as well as the findings of Okia et al in Uganda who found 8.3% with normocytic anemia, 50% microcytic anemia, and 41.7% macrocytic anemia. 9,10 Despite the discrepancies in the magnitude of the different types of the anemia detected, the general impression based on all these studies is that most pregnant women manifest with microcytc type of anemia. We associate this to irondeficiency problems commonly experienced by pregnant women more so the teenagers.…”
Section: Discussionmentioning
confidence: 99%
“…In various studies, the prevalence of dimorphic anaemia varies from 13 to 26% in India [ 22 , 27 , 28 ]. Reports suggest that it could more than 50% also [ 29 ]. Vitamin A was reported in 3.8% (95% CI: 1.2–6.4%) of women in reproductive age group as reported from a study from southern India [ 30 ].…”
Section: Approach and Analysismentioning
confidence: 99%